2007
DOI: 10.1126/science.1133061
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Organic Aerosols: Semivolatile Emissions and Photochemical Aging

Abstract: Most primary organic-particulate emissions are semivolatile; thus, they partially evaporate with atmospheric dilution, creating substantial amounts of low-volatility gas-phase material. Laboratory experiments show that photo-oxidation of diesel emissions rapidly generates organic aerosol, greatly exceeding the contribution from known secondary organic-aerosol precursors. We attribute this unexplained secondary organic-aerosol production to the oxidation of low-volatility gas-phase species. Accounting for parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

86
2,043
9
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,851 publications
(2,150 citation statements)
references
References 25 publications
86
2,043
9
12
Order By: Relevance
“…A large burden of long-chain (>C 10 ) alkanes has been proposed based on observations of SOA in large urban centers and analysis of diesel exhaust (Robinson et al, 2007). Since long-chain alkanes have high nitrate formation branching ratios (∼35%), adding them to our inventory could bring the observed and calculated branching ratios into agreement.…”
Section: Ans Sources In Mexico Citymentioning
confidence: 56%
“…A large burden of long-chain (>C 10 ) alkanes has been proposed based on observations of SOA in large urban centers and analysis of diesel exhaust (Robinson et al, 2007). Since long-chain alkanes have high nitrate formation branching ratios (∼35%), adding them to our inventory could bring the observed and calculated branching ratios into agreement.…”
Section: Ans Sources In Mexico Citymentioning
confidence: 56%
“…[57][58][59][60][61][62] Indeed, there may be a reservoir of such semi-volatile organics that are not currently measured in air but contribute to SOA formation. [63][64][65] This would help to reconcile the difference between predicted SOA concentrations in air and the measured values, which can be as much as an order of magnitude greater than predicted. 66,67 Finally, it had been thought for many years that the uptake of gases into particles and their subsequent reactions in the condensed phase in the atmosphere could be treated in terms of well-known physical (e.g., diffusion in the gas and liquid phases, mass accommodation at the surface) and chemical processes.…”
Section: Introductionmentioning
confidence: 93%
“…Emissions of anthropogenic LVOCs, SVOCs, IVOCs, and VOCs (i.e., aromatics, alkanes, olefins) from fossil and biofuel combustion are derived from the CMIP5 emission inventory for the RCP4.5 scenario (Thomson et al, 2011). The volatility distribution of anthropogenic emissions to LVOCs (8 %), SVOCs (72 %), and IVOCs (170 %) is based on the findings of Robinson et al (2007) and includes increased factors (the sum of the emission factors is 250 %) to account for missing IVOC emissions from the traditional inventories. More details about the organic compound emissions used here can be found in Tsimpidi et al (2016).…”
Section: Emission Inventory Of Oa Precursorsmentioning
confidence: 99%
“…Robinson et al (2007) demonstrated that OA emissions are semi-volatile and most of the emitted OA moves to the gas phase after emission due to dilution and evaporation. On the other hand, all organic vapors are subject to photochemical reactions with OH in the gas phase, forming organic products with lower volatility that can recondense to the particulate phase as secondary organic aerosol (SOA).…”
Section: Introductionmentioning
confidence: 99%